How Rural Public Libraries Support Local Economic Development in the Mountain Plains. Issue 3 (4th May 2021) - Hughes, Cynthia; Boss, Stephen
ABSTRACT: Economic and societal challenges continue to impact rural areas across the United States. This is especially true in the western mountain and plains states where populations are small. Towns are often far from one another and separated by geological features that can cause more physical isolation. Libraries are often the only sites with good public internet, meeting spaces, and knowledgeable staff able to navigate the available information resources. This article surveyed the lay of the community landscape in the mountains and plains region and noted resources related to economic development for librarians. Resources are included that are inexpensive yet highly effective in helping their communities grow businesses and economic opportunities.